2014
DOI: 10.1179/1743284713y.0000000448
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tempering on microstructure and mechanical properties of Ti alloyed 13Cr supermartensitic stainless steel

Abstract: Tempering is the final heat treatment applied to martensitic steels. In conventional martensitic stainless steels or in the newly developed supermartensitic grades, the mechanical properties are strongly influenced by tempering. In the present work, several tempering treatments were performed in a Ti alloyed supermartensitic stainless steel. Tensile mechanical properties, hardness and impact toughness were measured and correlated to microstructural features. Microstructural analysis was conducted in a field em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The minimum toughness at À46 C and maximum hardness were obtained in the specimen QT-500. Tempering at 500 C promotes secondary hardening and temper embrittlement, as already observed in supermartensitic 13%Cr steel [12]. The Table 2 e Identification of specimens and heat treatments.…”
Section: Resultsmentioning
confidence: 92%
“…The minimum toughness at À46 C and maximum hardness were obtained in the specimen QT-500. Tempering at 500 C promotes secondary hardening and temper embrittlement, as already observed in supermartensitic 13%Cr steel [12]. The Table 2 e Identification of specimens and heat treatments.…”
Section: Resultsmentioning
confidence: 92%
“…Steels with such complex chemical compositions may present a microstructure with not only martensite but also austenite and ferrite phases, depending on the heat treatment. For instance, quenching and tempering at 650 o C produced a microstructure of tempered martensite, reverse austenite, and fine carbides, with excellent low temperature toughness in a Ti-alloyed 12-13%Cr SMSS steel 3,4 . Delta ferrite islands may be found in the heat affected zone (HAZ) and in higher Cr and Mo grades.…”
Section: Introductionmentioning
confidence: 99%
“…Bilmes et al 17 reported the increase of *e-mail: ssmtavares@terra.com.br toughness with double tempering treatments and attributed to the increase of reverse austenite and the TRIP effect. On the other hand, double tempering makes the cost and duration of PWHT increase, and the difference of mechanical properties to the single tempered material may not be significant 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Detailed investigation by scanning electron microscopy (SEM) was conducted in samples polished and etched with Villela's reagent (90 ml H 2 O, 10 ml HCl, 1 g picric acid (C 3 H 3 N 3 O 7 ). The austenite volume fraction of specimens Q1-650, Q2-650 and Q3-650 were determined by magnetization saturation tests following the procedure suggested by Cullity 7 and used in previous works 4,5 . Electron backscattered scanning diffraction (EBSD) was performed in specimens Q1, Q2 and Q3 to determine the previous austenite grain sizes, but only a qualitative result was obtained, as will be shown.…”
Section: Methodsmentioning
confidence: 99%
“…Toughness is one of the properties which is most affected by these treatments. In previous works [4][5] it was observed the temper embrittlement phenomena in SMSS 13%Cr tempered in the 400 o C -600 o C range. This type of embrittlement is easily observed in conventional martensitic stainless steels tested at room temperature 6 , but in SMSS the temper embrittlement was only perceptible in impact tests at lower temperatures, such as -46 o C 4-5 .…”
Section: Introductionmentioning
confidence: 99%